Visual Detection of Lead Ions (Pb²⁺) Using a Colorimetric Sensor for Fishery Products - Ahmad Fudhail; Rizal Irfandi (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
The presence of lead ions (Pb²⁺) in fishery products poses potential risks to human health. Therefore, simple, rapid, and easily applicable detection methods are highly required. This study aimed to develop a simple colorimetric sensor for the visual detection of Pb²⁺ based on color change as an analytical signal. The sensor was prepared through the interaction of a complexing indicator with the target metal ion, resulting in a distinct and visually observable color response. The novelty of this work lies in the application of a simple colorimetric sensor with a low visual detection limit and high selectivity toward Pb²⁺, as well as its direct applicability to simulated fishery product samples without the need for complex analytical instruments. The results demonstrate that the developed sensor is capable of selectively detecting Pb²⁺ with a clear visual response, indicating its potential use as a low-cost and practical method for preliminary screening of lead contamination.